An Analysis of Unit Shift Translation Moonlight Movie into Bahasa Indonesia - Simamora, Riris (LP3kM Buddhi Dharma University, 2022)
The objectives of this research is to find out the pattern of unit shift in movie subtitle. The data in this research is taken from movie “moonlight”. This movie release in 2016, written and directed by Barry Jenkins. Based on Catford (1965) theory, the writer analyse this unit shift of translation based on five levels; morpheme, word, phrase, clause and sentence. The methodology used in this research is qualitative descriptive method. This research conducted by watching, reading and comparing the English subtitle and the Indonesian Subtitle. Then, the writer compared unit shift from source language to target language data. The data are clasiffied based on the pattern of unit translation. From the analysis, the writer found eeleventh unit shift pattern in the translation of “Twelve Years a Slave”, they are; shift from morpheme to word level, word to phrase level, word to clause level, phrase to word level, phrase to clause level, phrase to sentence level, clause to phrase level, clause to sentence level, sentence to word level, sentence to phrase level and sentence to clause level. 10 unit shifts from word level are translated into the other levels or similar to 19.2 % from the total of unit shifts of all levels;18 unit shifts from phrase level are translated into the other levels or similar to 34.7% from the total of unit shifts of all levels;9 unit shifts from clause level are translated into the other levels or similar to 17.3% from the total of unit shifts of all levels; 11 unit shifts from sentence level are translated into the other levels or similar to 21.1% from the total of unit shifts of all levels.